2017
DOI: 10.1111/jnc.14249
|View full text |Cite
|
Sign up to set email alerts
|

Reduced blood‐brain barrier expression of fatty acid‐binding protein 5 is associated with increased vulnerability of APP/PS1 mice to cognitive deficits from low omega‐3 fatty acid diets

Abstract: Lower levels of the cognitively beneficial docosahexaenoic acid (DHA) are often observed in Alzheimer's disease (AD) brains. Brain DHA levels are regulated by the blood-brain barrier (BBB) transport of plasma-derived DHA, a process facilitated by fatty acid-binding protein 5 (FABP5). This study reports a 42.1 AE 12.6% decrease in the BBB transport of 14 C-DHA in 8-month-old AD transgenic mice (APPswe, PSEN1ΔE9) relative to wild-type mice, associated with a 34.5 AE 6.7% reduction in FABP5 expression in isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…For behavioral studies, the number of animals used was determined from a previous study (Pan et al . ), where an effect on behavioral outcomes was detected. Since Nna1 KO mice showed obvious cerebellar ataxia after onset of the pcd phenotype, no blinding was performed for behavior tests.…”
Section: Methodsmentioning
confidence: 97%
“…For behavioral studies, the number of animals used was determined from a previous study (Pan et al . ), where an effect on behavioral outcomes was detected. Since Nna1 KO mice showed obvious cerebellar ataxia after onset of the pcd phenotype, no blinding was performed for behavior tests.…”
Section: Methodsmentioning
confidence: 97%
“…, ), observations of reduced BBB trafficking of DHA in mouse models of AD (Calon ; Pan et al . ) suggest that reversing BBB dysfunction associated with DHA trafficking in AD could hold therapeutic potential. We have demonstrated that the levels of a key BBB trafficking protein FABP5 are diminished in a mouse model of AD (Pan et al .…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that the levels of a key BBB trafficking protein FABP5 are diminished in a mouse model of AD (Pan et al . ) and postulate that approaches aimed at increasing the levels of FABP5 could restore brain DHA levels in AD. As DHA itself can affect PPAR activation and PPAR activation may be involved in regulation of FABP5 (Armstrong et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier metabolomics study showed that the extracellular concentration of endogenous unesterified DHA is higher than the intracellular concentration at the steady state in FATP1‐overexpressing human embryonic kidney 293 cells (Ochiai et al ). Furthermore, the protein amount of FATP1 in brain homogenate of AD model mice (amyloid precursor protein (APP)/PS1 mice) is decreased (Pan et al ). On the basis of these reports, we hypothesized that the expression level of FATP1 is decreased at the abluminal membrane of brain capillary endothelial cells by the accumulation of Aβ, resulting in a decrease in transport of unesterified DHA from brain capillary endothelial cells into the brain via FATP1.…”
mentioning
confidence: 99%